Bacteriological Profile And Antibiogram Pattern In Patients With Respiratory Tract Infection - Bhandari, R.; Rana, B.; Chaudhary, A.; Pandey, M.; Shrestha, G.; Regmi, R.; Khadka, R. B.; Kari, K. D.; Neupane, B. (Devdaha Medical Journal, 2024)
Introduction: Globally, respiratory tract infections are serious infectious disease affecting the organ of respiratory tract. A distinct group of microbes including bacteria, virus, fungus and parasite are associated with respiratory tract infection and is the leading cause of high morbidity and mortality. This study was conducted to determine the prevalence of bacteria associated with respiratory with antimicrobial susceptibility testing.Methods: This is a hospital-based cross-sectional study conducted between March, 2022 and June, 2023 among patients who visited Crimson Hospital of Butwal with respiratory tract infection. Bargery’s standard procedure has been followed for the isolation and identification of bacteria. Antimicrobial susceptibility testing was performed based on the Clinical & Laboratory Standard Institute (CLSI) guidelines.Results: Out of 358 only 186 (52.05%) respiratory samples showed bacterial growth. A total of 332 bacterial isolates were identified, comprising 203 (61.1%) Gram-positive and 129 (38.85%) Gram-negative bacteria. Among gram-positive isolates Staphylococcus aureus (30.7%, n=102) and Coagulase-Negative Staphylococcus (25.6%, n=85) were the most predominant. In contrast, Escherichia coli 13.2% (44) and Klebsiella pneumoniae 9.6% (32) were the predominant gram-negative bacteria isolates. Gram-positive bacterial isolates exhibited complete sensitivity to Vancomycin and Linezolid (100%), while, gram-negative bacterial isolates showed considerable sensitivity to Tetracycline (82.9%) and Cefuroxime (75%)Conclusion: A high prevalence of respiratory tract infection caused by a distinct group of bacterial pathogens has been reported. High number of Methicillin resistant Staphylococcus aureus (MRSA), Extended Spectrum Beta-lactamase (ESBL), and Multi-drugs Resistant (MDR) producing bacteria were detected.